PENGARUH PENGGUNAAN SARANA DAN PRASARANA PEMBELAJARAN TERHADAP PENINGKATAN KUALITAS MAHASISWA PROGRAM STUDI PPKN UNIVERSITAS PGRI SEMARANG - Aprilian, Rizki; Sutono, Agus; Purwosaputro, Supriyono (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2025)
This study aims to compare research design. The population studied comprises active PPKn students, with a sample selected randomly using a random sampling technique. The classical assumption tests in this study include normality, multicollinearity, and heteroscedasticity tests. Data collection was conducted through a questionnaire that had been previously tested for validity and reliability. Hypothesis testing in this study was carried out using two analytical models: simple linear regression and multiple linear regression. The results of this study indicate a significant impact of the use of facilities and the availability of infrastructure on the quality of students in the Pancasila and Civic Education program at PGRI University Semarang. Through this research, student quality can be measured using three indicators: knowledge, attitude, and skills. High-quality students are expected to have a good attitude towards their surroundings, possess extensive knowledge, and have proficient skills, thus being able to benefit to other.